Overcoming illiteracy through game-based learning in refugee camps and urban slums - Lauri Pynnönen; Lauri Hietajärvi; Kristiina Kumpulainen; Lasse Lipponen (Computers and Education Open, 2022)
Today 3.7 million refugee children are out of school. The ones forcibly displaced across borders are likely to remain there much of their childhoods and go through an entire school cycle in exile. Without access to quality education, these children have diminished likelihood of breaking free from circular dependency, scarcity, and marginalization. At the same time education sectors globally are adapting to the inevitable increase of digital learning. This study was motivated by the potential availability of digital education, and it argues for non-formal digital game-based learning in refugee and low-resource environments, with a special focus on early literacy.The participants (N = 359) consisted of marginalized, most vulnerable, and out-of-school children aged between 5 and 8. They participated in interventions in Pakistan and Bangladesh for 90 days, two hours a day. The children played digital learning games at their own pace following the learning goals of their national curriculums. The learning outcomes were measured using the EGRA framework.The study found that the intervention children achieved or surpassed the learning gains of a control group studying through formal education. These results suggest that digital learning games show promise for improving early grade literacy, even in low-resource contexts.